2015
DOI: 10.1517/17425247.2015.1083973
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized gold nanoparticles improve afatinib delivery into cancer cells

Abstract: Objectives: A drug delivery system based on colloidal pegylated gold nanoparticles (PEGAuNPs) conjugated with the tyrosine kinase inhibitor afatinib was designed and tested for enhancing the drug activity against pancreatic and non-small cell lung cancer cells. Methods: PEGAuNPs were synthesized and characterized physicochemically. Confocal imaging was performed to evaluate the nanoparticle internalization in cancer cells. For cell cycle distribution analysis, conjugated nanoparticles and afatinib alone were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…This fact corroborated with the higher increase in the in vitro cytotoxicity verified to cells incubated with conjugated BTZ than with free BTZ ( Figure 5). Previous studies have demonstrated that PEGAuNPs did not affect the cell survival for the concentration range of 0.1 to 1.0 nM [15,23]. The cell survival of S2-013 and TERT-HPNE cells after exposure was found to be in the range of 42-5 % and 90-38 %, respectively, for a range of BTZ concentration of 0.01-2.93 µM ( Figure 5).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…This fact corroborated with the higher increase in the in vitro cytotoxicity verified to cells incubated with conjugated BTZ than with free BTZ ( Figure 5). Previous studies have demonstrated that PEGAuNPs did not affect the cell survival for the concentration range of 0.1 to 1.0 nM [15,23]. The cell survival of S2-013 and TERT-HPNE cells after exposure was found to be in the range of 42-5 % and 90-38 %, respectively, for a range of BTZ concentration of 0.01-2.93 µM ( Figure 5).…”
Section: Resultsmentioning
confidence: 78%
“…They present high biocompatibility, stability and easy conjugation, non-toxicity and good uptake on human cells [15,16]. Recently, gold-based nanoparticles have been used to develop new agents as cancer imaging probes [17,18], as agents to enhance radiation therapy [19][20][21][22] and as drug delivery systems for cancer treatment [23][24][25]. Several studies reported that AuNPs in combination with chemotherapy and radiotherapy improve therapy efficacy in different cancer types, including pancreatic and human lung cancers [15,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges of developing theranostics for lung cancer metastasis treatment include determining a specific receptor and ensuring the biological safety of the multi‐functional nanocarrier. [ 21–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…By targeting ErbB family receptors, AFT blocks a wide spectrum of cancer-associated ErbB-driven pathways, and thus has broader antitumor activity against receptors with acquired mutations that are resistant to the first generation of TKIs [13]. AFT exposed at low concentration in the tumor cells, which reduced their clinical uses [14]. Therefore, the targeted delivery of AFT has become a focus of scientific research.…”
mentioning
confidence: 99%